Contemporary Geopolitical Positionings of Iceland Towards 'Europe' and the Nordic States. (April 2016) - Jones, Alun; Clark, Julian
Abstract: In the context of the spatialities of Europeanisation, we demonstrate the manoeuvrability of states through the selection and deployment of geopolitical positioning strategies. Specifically, we highlight how geographic quantities (territory, location, resources, natural conditions) are bundled together to substantiate a mutable national interest as well as underpin the advocacy by states of particular geopolitical positionings. We argue that the diplomatic use of geographic quantities in state‐led efforts to structure and shape international interactions has demonstrable geopolitical consequences. Using the case study of Iceland, one of the first casualties of the international financial crisis, we examine this state's geopolitical repositioning towards 'EUrope' through use of geographical uniqueness and concomitant reaffirmation of Nordic closeness. We expose the diplomatic challenges to the use of geographical categories such as uniqueness in geopolitical (re)positioning towards the emerging 'EUropean' order.